2018
DOI: 10.1097/md.0000000000012204
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome comparison of polymethylmethacrylate bone cement with and without mineralized collagen modification for osteoporotic vertebral compression fractures

Abstract: A retrospective study of consecutive patients.The purpose of this study was to compare the clinical effect of biomimetic mineralized collagen (MC) modified polymethylmethacrylate (PMMA) bone cement and traditional PMMA bone cement for the treatment of osteoporotic vertebral compression fractures (OVCF).New fracture on adjacent level is the major postoperative complication of percutaneous vertebroplasty (PVP). The clinical incidence was 12.4% to 27.7%. The increased stiffness of the treated vertebral body cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Within the biomimetic MC, HA is a poorly crystallized nanoparticle, which is arranged periodically and orderly among the collagen molecules. The biomimetic MC possesses the same chemical composition and microstructure as the natural bone matrix of human body, which can provide a good microenvironment for the activity of bone cells and help guide the regeneration of bone tissue [ 11–14 ]. In this study, although the MSTS score of the MC group was initially better than that of the autogenous bone group, the Lane–Sandhu X-ray score of the MC group was significantly lower in imaging with statistically significant difference at 1 month after the operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the biomimetic MC, HA is a poorly crystallized nanoparticle, which is arranged periodically and orderly among the collagen molecules. The biomimetic MC possesses the same chemical composition and microstructure as the natural bone matrix of human body, which can provide a good microenvironment for the activity of bone cells and help guide the regeneration of bone tissue [ 11–14 ]. In this study, although the MSTS score of the MC group was initially better than that of the autogenous bone group, the Lane–Sandhu X-ray score of the MC group was significantly lower in imaging with statistically significant difference at 1 month after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant animal experiments have shown that the biomimetic MC can effectively guide bone tissue regeneration and repair bone defect. After using in traumatic bone defect and bone fusion after spinal surgery, it has a good performance in guiding bone regeneration [ 11–14 ]. However, for the bone defect induced by curettage of benign bone tumors with high risk of recurrence and pathological fracture, clinical observation of the treatment of such bone defect by using biomimetic MC was not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, bone cement is the part of operation as well. Mineralized collagen polymethyl methacrylate (MC-PMMA) bone cement has better bioabsorbability and improved biocompatibility [46][47][48]. At present, MC-PMMA have been used and reported in three researches, but the results were mixed.…”
Section: Reform Surgical Operationmentioning
confidence: 99%
“…At present, MC-PMMA have been used and reported in three researches, but the results were mixed. Three studies [46][47][48] were all retrospective including 245 cases. Among of them, 133 cases in MC-PMMA group and 112 case in PMMA group.…”
Section: Reform Surgical Operationmentioning
confidence: 99%
“…[28][29][30] Via the modification, bone formation at the interface between the bone cement and host bone could be observed, and secondary fracture was significantly decreased as shown by longterm follow-ups. [31][32][33] Although MC-modified PMMA bone cement has many advantages compared with traditional bone cement, it has not been used for interbody fusion. Moreover, an appropriate biomaterial and applicable operative method need to be developed.…”
Section: Introductionmentioning
confidence: 99%